Customers Awareness on Green-Based Practicess Empirical Study on Service Industries In Indonesia - Kardison Lumban Batu; Januardi M. Diah; Mahendra Jaya (Inovbiz: Jurnal Inovasi Bisnis, 2021)
Current research is aimed at exploring the consequences of green based implementation in service industries in Indonesia. This study postulated eight hypotheses. A-survey questionnaire-based was used to collect data from Indonesia services industries, this study use the information multi-sources, data such as opinions, ideas, attitude, experiences, individual and group characters are becoming research subjects.  Empirical model with five exogenous variables and one endogenous required 490 samples with 27 parameters. Determining sampling measurement, Proportional samples was taken on service industries in Indonesia. Purposive sampling with non-probability sampling or judgmental was deployed to gain the data. SEM With Amos 24 statistical software was used to analyze data. Statistical outputs demonstrated that seven hypotheses proposed were accepted but the impact of green image on green purchase intention was rejected